1989
DOI: 10.1001/jama.1989.03430120100029
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Treatment of Depressed and Nondepressed Alcoholics

Abstract: We assessed the efficacy of lithium carbonate in the treatment of 457 male alcoholics in a double-blind, placebo-controlled Department of Veterans Affairs Cooperative Study. Alcoholics either without depression or with a history of major depression, current major depression, or dysthymic disorder were studied. Two hundred eighty-six alcoholics without depression and 171 alcoholics with depression began the 52-week outpatient study; 172 alcoholics (60.1%) without depression and 108 alcoholics (63.2%) with depre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(30 citation statements)
references
References 17 publications
(4 reference statements)
1
29
0
Order By: Relevance
“…Follow-up completion rates in these studies ranged from 48 to 93% (median 70%). The remaining 6 studies (Altintoprak et al, 2008;Dorus et al, 1989;Janiri et al, 1996;Mason et al, 1996;Paparrigopoulos et al, 2010;Petrakis et al, 2007) were excluded from the meta-analysis because their reported outcomes were not clearly identified as relating to the intention-to-treat sample.…”
Section: Insert Table 1 About Herementioning
confidence: 99%
“…Follow-up completion rates in these studies ranged from 48 to 93% (median 70%). The remaining 6 studies (Altintoprak et al, 2008;Dorus et al, 1989;Janiri et al, 1996;Mason et al, 1996;Paparrigopoulos et al, 2010;Petrakis et al, 2007) were excluded from the meta-analysis because their reported outcomes were not clearly identified as relating to the intention-to-treat sample.…”
Section: Insert Table 1 About Herementioning
confidence: 99%
“…In addition to antidepressants, other medications have also been tested with depressed alcoholic patients. Alcoholic patients, with or without depression, were randomized to receive either lithium or placebo (Dorus et al, 1989). No significant difference was found between the 2 groups on many depressive and alcohol outcome measures.…”
Section: Initial Abstinencementioning
confidence: 99%
“…drinking frequency and amount of alcohol consumption (Garbutt et al, 1999). While the results of some studies showed that lithium reduced drinking in alcohol-dependent patients with mood disorders (Fawcett et al, 1984;Merry et al, 1976), a randomized controlled trial (RCT) failed to demonstrate any benefit of this drug in either depressed or non-depressed patients (Dorus et al, 1989). The efficacy of selective serotonin reuptake inhibitors (SSRIs) remains to be tested in placebo-controlled, randomized trials with large sample sizes.…”
Section: Introductionmentioning
confidence: 99%